MANAJEMEN PEMBIAYAAN PENDIDIKAN DALAM MENINGKATKAN MUTU SEKOLAH MENENGAH ATAS - Frizki Nurul Pasa; Irwanto Irwanto; Sri Juwita; Zaitun Husseina Nasution (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2025)
Abstract: Financial Management in Education is a crucial aspect in organizing education that aims to improve school quality. This article aims to analyze the role and implementation of financial management in education as an effort to enhance the quality of Senior High Schools (SMA). This study employs a library research method by reviewing various relevant literature such as books, scientific journals, educational policy reports, and government regulations related to school fund management. The analysis is conducted using a descriptive qualitative approach to illustrate the concepts, sources of funding, and the implications of financial management on educational quality.The findings indicate that effective financial management in education includes four main stages: budget planning, financial organizing, implementation, and supervision of educational funds. Well-planned, transparent, efficient, and accountable fund management has been proven to support various programs aimed at improving educational quality, such as providing facilities and infrastructure, enhancing teacher competence, and developing innovative learning activities. Sources of education funding at the Senior High School level include government funds (such as BOS and DAK), community contributions through school committees, and independent income from school business units. Diversification of these funding sources strengthens the school’s financial independence while also expanding public participation in educational administration.From the perspective of Islamic education, financial management must be carried out based on the principles of trustworthiness (amanah), justice, and public benefit (maslahah) to create blessings and social welfare. Thus, financial management functions not only as an administrative instrument but also as a moral and strategic tool in realizing quality, character-based, and competitive education. This article recommends that each school improve its managerial capacity in financial management and build a transparent, accountable, and sustainable supervisory system to ensure the implementation of quality and integrity-based education. Keywords: Educational Finance Management, School Quality, Senior High School, Transparency, Islamic Education. Abstrak: Manajemen pembiayaan pendidikan merupakan aspek yang sangat penting dalam penyelenggaraan pendidikan yang berorientasi pada peningkatan mutu sekolah. Artikel ini bertujuan untuk menganalisis peran dan implementasi manajemen pembiayaan pendidikan dalam upaya meningkatkan mutu Sekolah Menengah Atas (SMA). Penelitian ini menggunakan metode studi pustaka (library research) dengan menelaah berbagai literatur relevan, seperti buku, jurnal ilmiah, laporan kebijakan pendidikan, serta peraturan pemerintah yang berkaitan dengan pengelolaan dana sekolah. Analisis dilakukan secara deskriptif kualitatif untuk menggambarkan konsep, sumber pembiayaan, serta implikasi manajemen keuangan terhadap mutu pendidikan.Hasil kajian menunjukkan bahwa manajemen pembiayaan pendidikan yang efektif mencakup empat tahapan utama, yaitu perencanaan anggaran, pengorganisasian keuangan, pelaksanaan, dan pengawasan dana pendidikan. Pengelolaan dana yang dilakukan secara terencana, transparan, efisien, dan akuntabel terbukti mampu mendukung berbagai program peningkatan mutu pendidikan, seperti penyediaan sarana dan prasarana, peningkatan kompetensi guru, serta pengembangan kegiatan pembelajaran yang inovatif. Sumber pembiayaan pendidikan di SMA meliputi dana pemerintah (seperti BOS dan DAK), sumbangan masyarakat melalui komite sekolah, serta pendapatan mandiri dari unit usaha sekolah. Diversifikasi sumber dana tersebut memperkuat kemandirian finansial sekolah sekaligus memperluas partisipasi publik dalam penyelenggaraan pendidikan.Dalam perspektif pendidikan Islam, pembiayaan pendidikan harus dikelola berdasarkan prinsip amanah, keadilan, dan maslahah agar dapat menciptakan keberkahan serta kemanfaatan sosial. Dengan demikian, manajemen pembiayaan tidak hanya berfungsi sebagai instrumen administratif, tetapi juga sebagai alat moral dan strategis dalam mewujudkan pendidikan yang bermutu, berkarakter, dan berdaya saing. Artikel ini merekomendasikan agar setiap sekolah meningkatkan kapasitas manajerial dalam pengelolaan keuangan, serta membangun sistem pengawasan yang transparan, akuntabel, dan berkelanjutan, guna menjamin terselenggaranya pendidikan yang berkualitas dan berintegritas. Kata Kunci: Manajemen Pembiayaan Pendidikan, Mutu Sekolah, Sekolah Menengah Atas, Transparansi, Pendidikan Islam.